Intracranial pressure monitoring and caesarean section in a patient with von Hippel-Lindau disease and symptomatic cerebellar haemangioblastomas. Issue 1 (February 2015) - Hallsworth, D.; Thompson, J.; Wilkinson, D.; Kerr, R.S.C.; Russell, R.
Highlights The natural history of von Hippel-Lindau disease in pregnancy is uncertain. The management of general anaesthesia for caesarean section using intracranial pressure monitoring is described. No sustained rise in intracranial pressure was demonstrated during caesarean section.